Late Pleistocene echimyid rodents (Rodentia, Hystricognathi) from northern Brazil - Ferreira, Thais M. F. (2016)
Echimyidae (spiny rats, tree rats and the coypu) is the most diverse family of extant South American hystricognath rodents (caviomorphs). Today, they live in tropical forests (Amazonian, coastal and Andean forests), occasionally in more open xeric habitats in the Cerrado and Caatinga of northern South America, and open areas across the southern portion of the continent (Myocastor). The Quaternary fossil record of this family remains poorly studied. Here, we describe the fossil echimyids found in karst deposits from southern Tocantins, northern Brazil. The analyzed specimens are assigned to Thrichomys sp., Makalata cf. didelphoides and Proechimys sp. This is the first time that a fossil of Makalata is reported. The Pleistocene record of echimyids from this area is represented by fragmentary remains, which hinders their determination at specific levels. The data reported here contributes to the understanding of the ancient diversity of rodents of this region, evidenced until now in other groups, such as the artiodactyls, cingulates, carnivores, marsupials, and squamate reptiles.